Analisis Integratif Motivasi dan Gaya Belajar dalam Meningkatkan Prestasi Atlet O2SN di Sekolah Dasar - Dudung; Tedi Supriyadi; Rizal Ahmad Fauzi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to conduct an in-depth analysis of student motivation and learning styles in relation to achieving success in the National Student Sports Olympiad (O2SN) at the elementary school level. Disparities in achievement across schools indicate that athlete development programs have not fully accounted for students' motivational characteristics and learning styles, often resulting in training processes that rely on a uniform approach. This study employs a qualitative approach using a case study method. Participants included O2SN student-athletes, school principals, teacher-coaches, and parents, selected through purposive sampling. Data were collected via in-depth interviews, observation, and documentation, and analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. The results indicate that both intrinsic and extrinsic motivation play a crucial role in shaping training enthusiasm, discipline, self-confidence, and perseverance among students participating in sports development programs. Furthermore, the application of instructional strategies tailored to visual, auditory, and kinesthetic learning styles enhances the effectiveness of mastering sports techniques during training. Support from principals, teachers, coaches, and parents, alongside the availability of adequate facilities and infrastructure, serves to reinforce the success of O2SN athlete development. The findings underscore that integrating motivation, learning styles, and school environment support forms a vital foundation for establishing an effective, adaptive, and sustainable sports development system capable of boosting O2SN athlete achievement at the elementary school level. Keywords: Learning Styles, Motivation, O2SN, Sports Development, Sports Achievement